2022
DOI: 10.3390/logistics6030043
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain for Ecologically Embedded Coffee Supply Chains

Abstract: Background: This research aims to identify how blockchain technology could support the ecological embeddedness of the coffee supply chain. Ecological embeddedness is a subset of the circular economy (CE) that demands legitimacy through design changes to product, production and/or packaging for benefits to economic actors and the environment. This is in contrast with legitimacy as a public relations exercise. Blockchain is a digital transformation technology that is not fully conceptualized with respect to supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…Thiruchelvam et al [59] and also Alamsyah et al [60], for example, analyze the blockchain considering the technical aspects more. Trollman et al [61] based their research on the ecological point of view of the blockchain. Other papers consider not only the technology but also the organizational point of view [62].…”
Section: Methodsmentioning
confidence: 99%
“…Thiruchelvam et al [59] and also Alamsyah et al [60], for example, analyze the blockchain considering the technical aspects more. Trollman et al [61] based their research on the ecological point of view of the blockchain. Other papers consider not only the technology but also the organizational point of view [62].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, increasing the transparency of blockchain traceability systems is a powerful means of reducing waste [ 176 ]. It was then suggested that the use of blockchain technology for agricultural by-products and final waste use would contribute to sustainable development [ 177 ].…”
Section: Challengesmentioning
confidence: 99%
“…At the distribution level, IoT-based blockchain technology is increasingly used for fruits and vegetables for real-time tracking and tracing purposes ( Trollman et al, 2022 ). In addition, IoT is being used for better management of stocks in warehouses ( Jagtap et al, 2021a ), and for road traffic congestions, BD is being utilised ( Jagtap et al, 2021b ; Zhang, 2013 ) for enhancing vehicle performance through predictive maintenance, and blockchain for encrypting important contract documentations and eliminating intermediaries.…”
Section: Digitalisation In Agriculture and The Food Industrymentioning
confidence: 99%